Effects of estradiol or progesterone on principal cells from amygdala complex evaluated in silico. - Medina-Maldonado, Venus; Eblen-Zajjur, Antonio (Revista Mexicana de Neurociencia)
Introduction: Amygdala neuronal responses play a key role in fear conducts. Principal Neuron (PN) is one of the most important generators of the output in the amygdala neuronal network. PN has excitatory connections to other PN and receives inhibitory synapsis from GABAergic interneurons acting on gGABAA, also receives thalamic and cortical inputs which activate postsynaptic gNMDA, gAMPA and gL (L-type Ca2+ channels). It has been proposed that main neurotransmission in amygdala could be modulated by estradiol (ES) and/or progesterone (PRG). Objetive: To implement a deterministic PN model with reported membrane conductances and to evaluate discharge changes induced by ES and/or PRG. Methods: Seven different scenarios were tested: a) Control conditions running unchanged membrane ion and synaptic currents; b) 20% reduction in GABAA current for ES effect; c) 20% increase in AMPA and NMDA currents for ES effect; d) b + c; e) 20% reduction AMPA/Kainate for PRG effects; f) 20% increase GABAA current for PRG effects; and, g) e + f. Results: ES shows a strong excitatory effect more dependent on gGABAA reduction associated with a long lasting increase of gAMPA than for the increase on gAMPA and gNMDA when evaluated separately, however, a combination of these factors, which are the actual situation, shows a more intense and lasting neuronal excitation. PRG shows a strong inhibitory effect avoiding any discharge that was more depended to the fast increase and long lasting effect on gGABAA than due to decrease in gAMPA and gNMDA. Combination of these factors shows no synergic, not even additive inhibitory effects.Conclusion: These results strongly support the notion that ES and/or PRG participate on amygdala principal neuronal responses involved in fear, anxiety and nocifensive behavior probably associated to gender.